Chemical, Microbiological, and Sensorial Properties of Bio-ayran Prepared using various Cultures - Hassan, Amina Mahmoud; Shalabi, Ola Mohamed; Ismail, Magdy Mohamed; Kamal El-Menawy, Reham (Current Functional Foods, 2025)
BackgroundAyran is drinkable yoghurt that is prepared by mixing water, salt, and yoghurt, or by adding water to milk and inoculation with yoghurt culture and adding salt after fermentation.ObjectiveThis study investigates the effect of using classic, probiotic, EPS-producing and EPS-producing + probiotic (BB12) cultures on the chemical, microbiological and sensorial characteristics of drinkable dairy product ayran.MethodsFour treatments of ayran were made using classic yogurt culture (T1), ABT-5 culture (T2), exopolysaccharide (EPS) producing culture (YO-Flex Mild 1.0) (T3), and EPS-producing culture + Bifidobacterium animalis subsp. lactis BB12 (mixture culture) (T4).ResultsSample T2 had the lowest acidity values during the fermentation period. While sample T2 had the highest pH values, the total solids, fat, and total protein contents of the ayran treatments were unaffected by culture type. Mineral contents slightly decreased in samples T3 and T4. In comparison to other treatments, sample 4 had higher counts of S. thermophilus, L. delbrueckii subsp. bulgaricus, and Bifidobacterium. The recommended level of probiotic bacteria (107 cfu g−1) was exceeded for all treatments, particularly T4, and remained above (107 cfu g−1) until the end of storage. Moreover, Ayran, made with mixture culture (T4), received the highest sensory evaluation scores.ConclusionMixture culture (EPS-producing culture + BB12) is a good starter to make bioayran containing high counts of probiotics.
Keywords: probiotic